Latin american systemic therapy: is it only an illusion? - Rodriguez Ceberio, Marcelo (2016)
This article presents a critical but encouraging vision of systemic therapy in Latin America. Seen from the history of the first systemic investigations and its protagonists, to define what is psychotherapy from this perspective. Collect a series of impressions that enter in the therapy itself and the role of systemic psychologist, but the analysis is not reduced there: it is contextualized in different problems that affecting Latin countries. Understands that the role of psychologist as an active figure in different context, social, cultural, economic, health, among others and represents a catalyst in solving psychosocial problems, a corrective agent crisis, that is tos ay, angles detour in cybernetic terms.